Workplace Spirituality and Person–Organization Fit Theory: Development of a Theoretical Model. (September 2019) - Palframan, Jason T.; Lancaster, Brian L.
This article advances the theoretical and practical value of workplace spirituality by drawing on person–organization (PO) fit theory and transpersonal psychology to investigate three questions: (a) What antecedents lead individuals and organizations to seek and foster workplace spirituality? (b) What are the perceived spiritual needs of individuals, and how are those needs fulfilled in the workplace? and (c) What are the consequences of meeting spiritual needs as individuals perceive them? Using constructivist grounded theory, analysis of interview data from thirty-four participants located in organizations across the Netherlands, Ireland, the United Kingdom, and Portugal led to development of a workplace spirituality, PO fit model in which we propose reconciling self as a core factor of workplace spirituality. We note how through the process of reconciling self, workplace spirituality is related to meaning making and how an individual perceives their work environment as conducive to self-expression and inner purpose. Practical and theoretical implications are discussed, as are limitations of the study and ideas for future research.